2008
DOI: 10.1038/ja.2008.48
|View full text |Cite
|
Sign up to set email alerts
|

Neoechinulin A Protects PC12 Cells against MPP+-induced Cytotoxicity

Abstract: Neoechinulin A, an alkaloid from Eurotium rubrum, can protect neuronal PC12 cells against cytotoxicity of a potent oxidant, peroxynitrite. Because involvement of peroxynitrite has been suggested in the pathogenesis of Parkinson's disease, we assessed whether this alkaloid could also protect PC12 cells from the cytocidal action of 1-methyl-4-phenylpyridine (MPP ϩ ), a Parkinson's disease, which affects 0.1% of the population over the age of 40 years, is characterized by a progressive loss of dopaminergic neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Thus, the requirement of the simultaneous presence of the alkaloid with the neurotoxin for cytoprotection is consistent with the case of MPP ϩ -induced cytotoxicity. 16) These results suggest that antioxidant activity 14) and/or interaction of an unknown cellular target molecule with neoechinulin A plays a role in the cytoprotective action of neoechinulin A against rotenone.…”
Section: )mentioning
confidence: 82%
See 3 more Smart Citations
“…Thus, the requirement of the simultaneous presence of the alkaloid with the neurotoxin for cytoprotection is consistent with the case of MPP ϩ -induced cytotoxicity. 16) These results suggest that antioxidant activity 14) and/or interaction of an unknown cellular target molecule with neoechinulin A plays a role in the cytoprotective action of neoechinulin A against rotenone.…”
Section: )mentioning
confidence: 82%
“…In contrast to neoechinulin A, preechinulin showed no cytoprotection. The results demonstrate that in addition to MPP ϩ -induced cytotoxicity, 16) neoechinulin A is also effective against rotenone-induced cytotoxicity and that the presence of the C8/C9 double bond, which gives rise to a conjugated system across the indole moiety to the diketo- (A) Dependency of rotenone cytotoxicity on glucose availability in the culture medium. NGF-differentiated PC12 cells in 96-well plates were treated with the indicated concentrations of rotenone in either 50 ml or 100 ml of culture medium for 25 h, and viability was determined by the LDH assay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we found that the treatment of differentiated PC12 cells with neoechinulin A can render the cells resistant to oxidative/nitrosative stress derived from the superoxide (O 2 − ) and nitric oxide (NO) cogenerator 3-morpholinosydnonimine (SIN-1). 2,7,8) Subsequent studies also demonstrated that neoechinulin A can also impede the progression of PC12 cell death induced by 1-methyl-4-phenylpyridinium (MPP + ) 9) and rotenone, 10) both of which are well-established Parkinson disease-inducing neurotoxins. However, the cytoprotective mechanisms against SIN-1 and neurotoxins are probably different.…”
mentioning
confidence: 99%